Efferent Modulation of Stimulus Frequency Otoacoustic Emission Fine Structure - Zhao, Wei; Dewey, James B.; Boothalingam, Sriram; Dhar, Sumitrajit (Frontiers in Systems Neuroscience, 2015)
Otoacoustic emissions, sounds generated in the inner ear, have become a convenient non-invasive tool to examine the efferent modulation of cochlear mechanics. Activation of the medial olivocochlear efferents has been shown to generally reduce the magnitude of these emissions. When the effects of efferent activation on the detailed spectral structures of these emissions have been examined, a shift of the spectral patterns towards higher frequencies has been reported for distortion product and spontaneous otoacoustic emissions. Stimulus frequency otoacoustic emissions have been proposed as the preferred emission type in the study of efferent modulation due to the simplicity of their production leading to the possibility of clearer interpretation of results. The effects of efferent activation on the complex spectral patterns of stimulus frequency otoacoustic emissions have not been examined to the best of our knowledge. We have examined the effects of activating the medial olivocochlear efferents using broadband noise in normal-hearing humans. The detailed spectral structure of stimulus frequency otoacoustic emissions, known as fine structure, was recorded with and without contralateral acoustic stimulation. Results indicate that stimulus frequency otoacoustic emissions are reduced in magnitude and their fine structure pushed to higher frequencies by contralateral acoustic stimulation. These changes are similar to those observed in distortion product or spontaneous otoacoustic emissions and behavioral hearing thresholds. Taken together with observations made about magnitude and phase changes in otoacoustic emissions and hearing thresholds upon contralateral acoustic stimulation, all changes in otoacoustic emission and hearing threshold fine structure appear to be driven by a common set of mechanisms. Specifically, frequency shifts in fine structure patterns appear to be linked to changes in stimulus frequency otoacoustic emission phase due to contralateral acoustic stimulation.